An Assessment of Pre-diabetic and Diabetic Conditions among the Garo Population in Bangladesh - Munni, Ummy Salma; Islam, Khaleda (Bangladesh Journal of Nutrition, 2020)
Diabetes mellitus is one of the most common non-communicable diseases and has a major impact on public health worldwide. It causes a vast contribution to morbidity and mortality worldwide. Several factors like age, sex, BMI, hypertension, dyslipidemia may be potentially controlled or minimized leading to huge benefits in the management and prevention of prediabetes and diabetes. Many diabetes studies have been conducted in Bangladesh among the general population, but only a few have been conducted among the indigenous population. Garos are one of the important ethnic groups in Bangladesh but major non communicable disease, diabetes has not been assessed among them. The present study was undertaken to assess the diabetic and prediabetic conditions of the Garo population in Bangladesh. It was an observational analytic study with a cross-sectional design conducted among 106 Garo people from Mymensingh and Tangail districts of Bangladesh. The result of the study shows that 7.5% of the study population had a family history of diabetes and mean± SD fasting blood glucose level (mmol/L) was 5.42 ± 2.83. The study found that 13.2% had impaired fasting glucose or prediabetic and 7.6% was diabetic based fasting blood glucose (FBG). Among the study population, 2.8% of the diabetic patient took insulin. The study also revealed gender-based distribution of diabetes mellitus among males and females, where 9.6% of the female participants were diabetic, based FBG. In association with nutritional status, it was found that 9.5% of the underweight 5.7% of the normal weight individuals, 10.8% of the overweight participants were diabetic based on FBG. Positive correlation was observed between waist hip ratio (WHR) and fasting blood glucose level (r=0.23, p<0.05). The SBP (Systolic Blood Pressure) had a positive correlation with fasting (r=0.22, p<0.05). Hypertension, WHR and diabetic conditions were found to be correlated in this community. Bangladesh J. Nutr. Vol. 33, December 2020, P: 11-19